Les Frères musulmans au pouvoir et la question urbaine en Égypte : un rendez-vous manqué ? - Roman Stadnicki (Les Cahiers d’EMAM)
The article attempts to show that although the urban public action of the Muslim Brotherhood (in power in Egypt between 2012 and 2013) are not the root cause of their failure, they were an impetus for the social dispute to which they have been subjected. Therefore, it is for us to understand how this idea of the failure of the islamists’ urban action towards the population, and other urban actors, has circulated in Cairo. Initially, they have blamed the leaders of the Muslim Brotherhood for their inertia, before criticizing them for pursuing Mubarak’s urban policies – which were greatly contested by the revolutionaries – and then the adoption of coercive measures that mainly targeted the popular neighborhoods. This latest action being in total contradiction with the islamists’ previous action local-wide. But beyond the criticism of the political action of the Muslim Brotherhood, this paper aims at showing that it will require more than a transitional government to reverse the orientations regarding the socio-spatial’s division within Egyptian cities resulting from a number of decades of authoritarian and neoliberal urban policies.